An analytical study of the speed and distance of touching the ball with the playing field for the points of transmission and mutual strikes for the final of the Australian Open tennis tournament between the two players (Serena Williams - Maria Sharapova) - Habib, Rafid; Kamel , Alaa; Warwar , Adhwaa; Ahmed, Omar Saad (International Journal of Psychosocial Rehabilitation, 2020)
Studying and analyzing matches gives more accurate results than tests, exercises and experimental matches, given that the players make a more real effort in official matches compared to tests and training, and that the measured variables are biomechanically obtained from match analysis is an accurate and reliable measurement method for evaluating the performance of the team or player And to explain the reasons for winning and losing, and that one of the important biomechanical variables in the game of tennis is the distance of contact with the ball with the playing field and the sides of the field in addition to its speed. Most of the biomechanical research is concerned with performance analysis and dynamic performance variables. In this research, performance results have been analyzed, because the level of motor performance here is very high and a match is the final of the Australian Open tennis tournament for the year 2015, which ended with the victory of the American player (Serena Williams) over the Russian player ( Maria Sharapova) has two groups, and the number of runs in the first group (6-3) and in the second group (7-6), and through analyzing the performance results we reached the reasons for winning the American player, which achieved (28) points in direct and influential transmissions and an arithmetic mean of contact distance The ball with the ground pitch b G (0.420 cm), compared to (17) sending Russian player and a mean distance of the ball in contact with the pitch reached (0.594 cm). The results of the analysis also show that the arithmetic mean of the transmission speed of the American player was (181) km / hour, while the arithmetic mean of the Russian player was (161) km / hour. The results of the analysis also show that the American player achieved (39) points in resolving the mutual strikes rally, and the arithmetic mean of the distance of contact with the ball with the playing field reached (0.872) cm, compared to (37) points in resolving the mutual strikes rally, and the mean of the distance of contacting the ball with the playing field reached (0.961) cm, if we note that there are clear differences in favor of the American player in the number of points of transmission and the speed of transmission and the number of points for deduction of mutual strikes, as well as the difference is clear in the distance of contact of the ball with the pitch of the field in transmissions and mutual strikes.